Cardiac rehabilitation: Effective yet underutilized in patients with cardiovascular disease. Issue 11 (2nd September 2022) - Bracewell, Natalie J.; Plasschaert, Jeffrey; Conti, Charles Richard; Keeley, Ellen C.; Conti, Jamie B.
Abstract: Cardiac rehabilitation is a comprehensive program that treats patients with multiple cardiac conditions including post‐myocardial infarction, stable angina, post‐coronary artery bypass surgery, chronic heart failure, and peripheral vascular disease with structured exercise, and nutrition and risk factor counseling. It is an effective tool that has been shown to improve not only quality of life but also reduce adverse cardiac events, including death. While the value of cardiac rehabilitation is supported by a large body of evidence and its recommendation by the American Heart Association/American College of Cardiology it is significantly underutilized due to both patient and systemic factors. Continued efforts should be made to remove the obstacles to make cardiac rehabilitation available to all those who qualify.